Development of a Hybrid Model of Diffie–Hellman and Hill Cipher Based on Fuzzy Sets for Strengthening Cryptographic Key Security - Armayani Arsal; Muh. Fachrul Latief (Journal of Mathematics, Computations and Statistics, 2026)
In this paper, key security has been examined, which is a fundamental factor in cryptographic systems because the quality of the key significantly affects the algorithm's resilience against cryptanalysis attacks. This research aims to develop a hybrid cryptography model of Diffie-Hellman and Hill Cipher based on fuzzy sets. This hybrid model is designed by combining the advantages of Diffie–Hellman in the secure key exchange process with Hill Cipher as a matrix-based encryption algorithm. Fuzzy sets are used as an adaptive mechanism in the key generation and strengthening process to enhance the randomness, complexity, and uncertainty of the key value. The research methods include literature study, hybrid scheme design, fuzzy rule formulation, and implementation of encryption and decryption processes. The result of this research is the formation of a hybrid cryptography model capable of generating keys that are more difficult to predict, thereby strengthening data protection against potential cryptanalysis attacks.